Pass-Through Effects of the East African Community Common External Tariffs on Kenya's Domestic Prices - Justine Ongeri Mogendi; Tabitha Kiriti Nganga; Laura Nelima Barasa (Journal of Economic Integration, 2023)
This study offers an empirical microlevel analysis of the pass-through effects of the East African Community Common External Tariff on consumer prices in Kenya. Using data from the Kenya Integrated Household Budget Surveys conducted in 2005 and 2015, this research employs a fixed-effects model to estimate pass-through equations. The analysis focuses on consumer prices for agricultural and manufactured goods. It also considers household residential classifications, distinguishing between rural and urban areas, and it investigates the impact of border proximity and transportation costs on the pass-through effect. The findings show that manufactured goods have a significant pass-through effect. A 1% change in tariffs results in a 0.84% change in consumer prices for manufactured goods. However, the pass-through effects for agricultural goods were incomplete, suggesting that markets for manufactured goods are more competitive in Kenya. The study also found that pass-through effects vary depending on proximity to borders and the urban-rural divide.
Keywords: F12; F13; F14; F15; D21; R2; 330; Customs Union; Common External Tariff; Tariff Pass through; East African Community